Budidaya Ikan Nila Merah (Oreochromis SP.) Dengan Teknik Yumina Dan Bumina Sebagai Bisnis Yang Menguntungkan Bagi Masyarakat - Arfiana Dita Arum Sari; Dita Atasa; Yana Yana; Asep Syaefuddin; Dewi Suryani; Rhomi Ardiansyah (FKIP, Universitas Palangka Raya, 2023)
Fish is a biological resource in the form of aquatic biota which has the widest number and distribution on earth. The wide distribution of fish supports the large number of species diversity so that it occupies the largest percentage of vertebrate groups. SEAMEO BIOTROP (Southeast Asian Regional Center for Tropical Biology) is a Southeast Asian Ministers of Education’s Organization that provides programs for agricultural students. SEAMEO BIOTROP has several apprenticeship divisions, one of which is Sustainable Urban Agriculture Practitioner (PPB) which studies various problems and solutions to agriculture in the environment urban area. The sub-topic in the internship activities of the PPB division is Red Tilapia (Oreochromis sp.) cultivation with the Yumina and Bumina techniques which can be carried out in urban areas. The activities carried out include: 1. Seeding, 2. Maintenance, 3. Treatment. The purpose of this activity is to provide knowledge, understanding, and skills in cultivating red tilapia properly and correctly so that it can grow and generate large profits at harvest for the community.